THE KOMUZ OF 3 M: MANAS, MEN AND MANAGEMENT - NISAR AHMAD (Türk Uygarlığı Araştırma ve Uygulama Merkezi Dergisi, 2023)
Komuz is traditional Kyrgyz instrument with three strings. Three strings are played in unison to produce music. This paper attempts to synchronize the M of Manas with two other Ms of modern theory of man management. The phenomenon of civilization, as a heavily organized public body, springs from different sources and this process is deeply rooted in its stratum of space and time.1 Over a period of time the relationship between civilization, its sources, and its practice develop a cyclical relationship – the civilization and culture impact all aspects of the society including business and administration. For example introduction of faster modes of communication (information technology) has had its deep impact on society and cultures which in-turn has affected the way business and administration is organized – organizations have become lean with fewer layers of management. This process of interlinking between business management and civilization can be studied further through the study of classics. Manas is studied in this paper to study its linkages with organization and modern concepts of management.